Differences in Marketing Communication Activities at Sheraton Surabaya Hotel & Towers in the middle of COVID-19 Pandemic - Jiwangga Hadi Nata; Nur Emma Suriani; M Riza Darmawan (Universitas Airlangga, 2020)
The tourism industry is a growing industry where hospitality is an essential business that provides accommodation for tourists. However, in early 2020 there was a COVID-19 pandemic that affected the crisis in the tourism industry. The decline in the number of tourists and the limited tourism activities lead to a decrease in consumer buying interest and here also the role of the marketing communication department as a department that promotes and is a liaison between hotels and consumers. The role of marketing communication in increasing the buying interest of prospective consumers is one of the factors that has an impact because of the activities of the department that exchange information with potential customers. This study aims to determine the promotion and adaptation activities carried out by the marketing communication of the Sheraton Surabaya Hotel & Towers in facing a crisis due to the COVID-19 pandemic. In this study, researchers used qualitative methods where the data were analyzed first then arranged and explained with certain statements in the form of written or oral words from an informant and observing the place under study. The results of the study show that marketing communication department of the Sheraton Surabaya Hotel & Towers is adapting to crisis management and using soft selling while planning steps to be taken after the crisis has passed. Marketing communication activities also help to maintain the buying interest of potential customers. The results also show that the use of promotion through social media is more flexible in various conditions.